Nanostructured Titanium Dioxide: Synthesis, Characterization and Photoactive Application - Buabeng, F.P. (University of Ghana, 2016)
Dye pollutants contaminate water bodies when they are improperly disposed into the ecosystem. Effects caused by the disposal of these dye pollutants include aesthetic pollution, eutrophication and perturbations in aquatic life. This work aims to mitigate these water contamination problems by studying possible degradation of these pollutant compounds. Semiconductor photocatalytic process using nanocrystalline TiO2 as the semiconductor catalyst was adopted in this work to photodegrade Rhodamine B dye and Sudan III dye solutions by exposing it to UV light. In this work, we explored the synthesis of porous TiO2 nanostructured powders via chemical means such as the Sol gel and Hydrothermal techniques. The as-produced nanoparticles were then characterized via X-Ray Diffraction (XRD), Scanning Electron Microscopy (SEM), Brunauer–Emmett–Teller (BET) surface area analysis, Fourier Transform Infra-Red, and Raman Spectroscopy for their microstructure, morphology, optical, porosity and adsorption properties. The photocatalytic degradation of Rhodamine B and Sudan III dyes were studied at various exposure times to the UV light up to 150 minutes with 30 minutes interval. The XRD and Raman spectra of the samples showed that, the anatase phase of TiO2 was produced when the Sol gel method was used in the nanoparticles synthesis. The Hydrothermal method also resulted in the synthesis of anatase phase of TiO2 except the sample calcined at 600 °C which showed about 15% rutile phase. Fourier Transform Infra-Red spectrum on the TiO2 prepared by Sol gel method showed bands at 3228cm-1 and 1635 cm-1, which is attributed to O-H stretching and stretching of titanium carboxylate, respectively and these peaks were seen disappearing after calcining at different temperatures. Only the strong absorption between 800 and 410 cm-1 remained, which were attributed to the obtained TiO2 nanoparticles. The highest BET surface area was reported to be 207.7 m2/g which was assigned to the as-prepared TiO2 nanoparticles synthesized by the University of Ghana http://ugspace.ug.edu.gh Hydrothermal technique. The adsorption and desorption isotherms of this sample exhibited typical type IV pattern with hysteresis loop characteristic of mesoporous material according to the classification of IUPAC. 94% degradation of Rhodamine B dye was observed after 150 minutes irradiation of UV light when TiO2 catalyst synthesized by Sol gel technique and calcined at 300 °C was used in photodegrading Rhodamine B dye solution and a 100% degradation was seen after 150 minutes UV light irradiation in Sudan III dye when Hydrothermal prepared catalyst calcined at 300 °C was used. The SEM micrographs obtained also showed that nearly spherical TiO2 nanoparticles were produced. The present results obtained showed that a mesoporous spherical anatase TiO2 nanoparticles with high photocatalytic activity and high surface area were synthesized. They were highly crystalline with grain size ranging from 2 nm to 30 nm. These synthesized TiO2 nanoparticles can be applied in the degradation of wide range of dye pollutants.
Thesis(MPHIL)-University of Ghana, 2016
Keywords: Nanostructured Titanium Dioxide; Synthesis; Photoactive